IMPACT OF SOCIO-ECONOMIC CHARACTERISTICS OF RURAL HOUSEHOLDS ON FOOD SECURITY: THE CASE OF THE PUNJAB, PAKISTAN - M. K. Bashir; S. Schilizzi; R. Pandit (Journal of Animal and Plant Sciences, 2013)
Food security was assessed using the calorie intake method in the rural Punjab of Pakistan using primary data from 1152 households in 12 districts. Results show that 23% of households were food insecure, out of which about half were found to be severely food insecure. Socio-economic correlates were identified by analyzing cross-tabulations and running χ 2 tests. Livestock assets, monthly income, family size, family structure, household head’s age and educational levels were identified as major correlates of rural household food security. Furthermore, they were ranked for their relative importance to food security. Livestock assets and monthly income were found to be the most important factors.
Keywords: Food security; rural households; factor identification; factor ranking; Pakistan